Uji Kelayakan Usaha Board Game di Kota Sidoarjo - Timotius Bintoro Yananto; Nova Sepadyati (Jurnal Titra, 2020)
Many board games businesses have opened in Surabaya and many teenager are interested to playing it. This research is meant to determine the feasibility of board games business in Sidoarjo. The business feasibility study has three parameters namely market, technical and financial feasibility. Market feasibility is seen based on market segmentation, market target and market position. Technical feasibility is seen based on company’s operational management, location feasibility, layout determination, number and type of board game, and other supporting facilities. Financial feasibility is seen based on the result of payback period, net present value and internal rate of return. The research result shows that the board game business in Sidoarjo is feasible from the market, technical and financial perspective.